Modeling the one-dimensional inverse heat transfer problem using a Haar wavelet collocation approach - Ali Jahangiri; Samira Mohammadi (مجله مدل سازی در مهندسی, 2019)
In this paper, a numerical method is used to solve the one-dimensional inverse heat transfer problem, which is a combination of punctuation with wavelet collocation method and Tikhonov's method of stabilization. In order to validation of the heat transfer problem, the input data is used as including noise data ranging from 1 to 5%. Also, in this study, the Haar functions, in addition to estimating the unknown functions, are also used to reduce output noise. From the results, two main advantages of the repeated method have been proven, first, the precision of this method in estimating the unknown boundary condition and the second processing speed due to the lack of need for wavelet functions to be collocated at low intervals. This suggests that this method is also high speed. According to the obtained results it can be admitted that the present method maintains its sustainability with small error in input data.